2018
DOI: 10.1111/pedi.12641
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes distress is more strongly associated with HbA1c than depressive symptoms in adolescents with type 1 diabetes: Results from Diabetes MILES Youth-Australia

Abstract: Consistent with evidence from studies among adults, diabetes distress mediated the relationship between depressive symptoms and HbA1c among adolescents with type 1 diabetes. These findings suggest that clinicians need to be aware of diabetes distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 42 publications
10
58
0
Order By: Relevance
“…In addition, close associations between depressive symptoms and diabetes distress have been reported previously and discussed intensively. Previous studies suggest that diabetes distress and depressive symptoms partly overlap, but glycaemic control is more strongly associated with diabetes distress than with depressive symptoms . Our study complements previous results and confirms these findings in a previously non‐investigated group.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, close associations between depressive symptoms and diabetes distress have been reported previously and discussed intensively. Previous studies suggest that diabetes distress and depressive symptoms partly overlap, but glycaemic control is more strongly associated with diabetes distress than with depressive symptoms . Our study complements previous results and confirms these findings in a previously non‐investigated group.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the published works of the literature, we have described the landscapes of diabetes-specific distress on glycemic [19]. For example, a study from Australia suggested that diabetes-specific distress was more closely associated with HbA1c level than depressive comorbidity in adolescents with type 1 diabetes [22]. Moreover, Tsujii et al found that diabetes-specific distress, but not depressive symptoms, was associated with glycemic control among Japanese patients with type 2 diabetes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many studies have shown that diabetes-specific distress and depression comorbidity do not work alone but influence each other and interweave each other, which explain in a certain extent the reasons why the effect of diabetes-specific distress was left out [19,20]. However, diabetes-specific distress is more common and widespread than depression in patients with diabetes mellitus [21,22]. In view of this, the American Diabetes Association (ADA) proposes regular evaluations for patients with diabetes-specific distress for the management and prevention of severe diabetic complications [23].…”
Section: Introductionmentioning
confidence: 99%
“…These were stress, fear and worry, mealtime struggles, assumptions and judgments, feeling abnormal, and conflict. These indicators of diabetes distress relate both directly and indirectly to the ability to perform diabetes self-care and achieve glycemic control [ 4 , 37 - 39 ]. For example, individuals can be knowledgeable and capable but not follow through due to prioritization of issues of greater importance to them at the present time (eg, fitting in with peers).…”
Section: Discussionmentioning
confidence: 99%